The experiences of private somatology therapists on their self-management in a private practice - Karien Richter; Karien Jooste (AOSIS, 2013)
Somatology therapists have a demanding occupation, both physically and emotionally. Long working hours coupled with handling clients on a daily basis, notwithstanding the strain of ensuring high quality client care, are all aspects that place pressure on the therapist. These aspects, in the backdrop of a lack of self-management of a therapist, could result in impaired judgement and substandard performance in the workplace. The purpose of this study included exploring and describing the experiences of private somatology therapists in self-management, from which recommendations for improved self-management within private somatology practices were described. For the purpose of this study, self-management was defined as a method of managing not only the interaction with clients and work stressors, but also the feelings of the therapists, by practising a variety of techniques such as self-discipline. A descriptive, exploratory and contextual qualitative design was followed. The accessible population consisted of therapists (n = 15) practising at six private somatology facilities in the Pretoria North region. Purposeful sampling was followed. Ten individual unstructured interviews as well as a pilot study were conducted in which field notes were taken. Open-coding data analysis identified four themes with subthemes. Lincoln and Guba's model was used to ensure trustworthiness and ethical considerations were followed throughout the process. Informed consent was granted by the private somatology practices and the therapists. One of the themes indicated that self-management strategies should be displayed, in order to gain a sense of control. The study identified that there is a definite need to nurture the therapist within this demanding working environment which we call the somatology practice. Somatologie terapeute het 'n veeleisende werk hetsy fisies en emosioneel. Lang werksure, gekoppel met die hantering van kliënte op 'n daaglikse basis, asook die stremming om te alle tye 'n hoë gehalte kliëntesorg te verseker, is als faktore wat spanning op die terapeut plaas. Die gebrek aan selfbestuur van 'n terapeut - in die agtergrond van die bogenoemde bydraende faktore − kan tot 'n swak oordeelsvermoë en dienooreenkomstige substandaard optrede in die werkplek lei. Die doel van hierdie studie was onder andere om die ervarings van privaat somatologie-terapeute te ondersoek en te omskryf, waarvolgens aanbevelings vir verbeterde selfbestuur in privaat somatologie-praktyke beskryf was. Vir die doeleindes van hierdie study, word selfbestuur gedefinieër as 'n metode om nie alleenik die interaksies met die kliënte en die werkstressors te bestuur nie, maar ook om die gevoelens van die terapeute te bestuur, deur middel van die uitoefening van 'n verskeidenheid tegnieke, onder andere, self-dissipline. 'n Beskrywende, ondersoekende en kontekstuele kwalitatiewe ontwerp is gevolg. Die toeganklike populasie het uit terapeute (n = 15) in ses private somatologie-praktyke in die Pretoria-Noordstreek bestaan. 'n Doelgerigte steekproef is gevolglik geneem. Tien individuele ongestruktureerde onderhoude, asook 'n loodstudie is uitgevoer en veldnotas is geneem. Oop kodering het vier temas met subtemas geïdentifiseer. Die model van Lincolin en Guba is gebruik om betroubaarheid te verseker en etiese oorwegings is tydens die navorsingsproses gevolg. Ingeligte toestemming is deur die privaat kliniekpraktyke en deelnemers verleen. Een tema het inderdaad aangedui dat selfbestuurstrategieë gedemonstreer behoort te word om sodoende 'n gevoel van beheer te bekom. Hierdie studie het geidentifiseer dat daar 'n definitiewe behoefte is om die terapeut binne die veeleisende werksomgewing te koester wat ons die somatologiepraktyk noem.